Pengaruh Sarana Prasarana Laboratorium IPA Terhadap Motivasi Belajar Siswa di SMP Negeri 10 Jember Kelas 7 - Alufatuz Zakiyah; Indah Kurniawati; Annisa Nurul Firdaus; I. Ketut Mahardika (Peneliti.net, 2022)
This study aims to determine the management of the science laboratory consisting of (1) organization (2) implementation of (3) supervision (4) planning (5) laboratory facilities and direct evaluation in the science laboratory at SMPN 10 Jember. This study used qualitative research methods. Data collection techniques using interviews, observation, and documentation. In determining the assessment of student learning activities according to Paul B. Diedrich, they are classified into eight namely visual activities, oral activities, listening activities, writing activities, drawing activities, motor activities,mental activities, and emotional activities.